Kelayakan Finansial Dan Analisis Nilai Tambah (Value Added) Produk Non Pangan Berbahan Mangrove - Febrianti, Desy; Cesrany, Mahaldika; Putu Sri Dia Utari, Siluh (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
The use mangrove for non-consumable products. including for natural dyes and making edible films (food product preservatives). The aim of this research is to analyze business feasibility and analyze the added value of non-consumable processed products from mangrove forests. This research is a quantitative research using primary and secondary data obtained by observation and interview techniques at non-consumable mangrove forest product processors. The research was conducted from September 2022 to March 2023. The business feasibility analysis method is determined by calculating income, profits, Revenue Cost Ratio (R/C ratio), Break Event Point (BEP), Payback Period and Return Of Investment (ROI), while the method value added analysis was carried out using the Hayami 1987 method. The results showed that the business of processing mangroves into natural dyes and edible films was worth pursuing and profitable as indicated by a positive ROI value, R/C ratio > 1, sales BEP < selling price, production BEP > quantity production with PP < 1 year. The added value of the product in processed edible film is higher than the added value in processed natural dyes with a coefficient factor of 2 and a business owner's profit of 79.03% for natural dyes and a factor coefficient of 600 and a business owner's profit of 98.87% for edible film. The results can encourage mangrove processing activities as non-food products.